IMMUNOLOGICAL AND IMMUNOGENETIC MARKERS OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE UNDER THE CONDITIONS OF ENVIRONMENTAL ZINC DEFICIENCY - L. M. Karzakova; N. D. Ukhterova; L. V. Borisova; L. N. Ivanov (Медицинская иммунология, 2014)
Abstract. We have examined parameters of innate and adaptive immunity, as well as HLA profile in COPD patients living under the conditions of environmental zinc deficiency (Zn levels in the soil < 0.1 mg/kg, and dietary contents of zinc, 9.1 mg/d, as compared to normal lower limit of 15 mg/d). It was shown that the patients with COPD exhibited activation of adaptive humoral immunity, along with suppression of T cell-mediated response and decreased phagocytic activity of neutrophils. Carrier state of HLA-DRB1*11 и -DQB1*301 alleles in inhabitants of zinc-deficient areas is a predisposing factor for COPD development. Meanwhile, DRB1*01, DQА1*0101, DQВ1*0501 alleles may be suggested as markers of resistance to this disease. (Med. Immunol., vol. 10, N 6, pp 513-518).